THE INFLUENCE OF EMPLOYEE ENGAGEMENT, WORKPLACE RECREATION AND WORKPLACE DIVERSITY ON EMPLOYEE PRODUCTIVITY AT PT. WENANG PERMAI SENTOSA MANADO - Kumambong, Novita Regina; Pangemanan, Sifrid S.; AlfaTumbuan, Willem J.F (Universitas Sam Ratulangi, 2016)
Each company always want to have employees with a highly performance or productivity when work and also have ability to support company for a good performance to achieve the goal. More productivity means more outcomes, more outcomes mean more revenue, and having more revenue guaranteed the sustainability of the business. PT. Wenang Permai Sentosa is a